PENGARUH LIKUIDITAS, PROFITABILITAS DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN: (Studi Pada Perusahaan Sektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023) - Noni Nopita; Rizca Puspita Devi (Economicus : Jurnal Ekonomi dan Manajemen, 2024)
From 2019 to 2023, this study will look at textile and garment companies listed on the IDX to see how factors like liquidity, profitability, and activity affect company value. This research is based on numerical data. The sample population included 22 garment and textile firms listed on the Indonesia Stock Exchange. Using the purposive selection approach, six firms were selected to serve as the research objects in this study. Multiple linear regression analysis in SPSS is the data analysis strategy used. For the years 2019–2023, this research found no correlation between the textile and garment industry's listed companies on the Indonesia Stock Exchange (IDX) and measures of partial liquidity (CR) or profitability (ROA). During the period from 2019 to 2023, the Company Value of textile and garment sectors listed on the Indonesia Stock Exchange (IDX) is positively and significantly impacted by Activity (TATO). Between 2019 and 2023, the Company Value of textile and garment sectors listed on the Indonesia Stock Exchange (IDX) is significantly impacted by CR, ROA, and TATO all at once, with a significance level of 0.001<0.05.